PRACTICE OF SELLING AND BUYING GOODS PAID DEFINITELY WITH GOLD ASSURANCE IN PERSPECTIVE LAW ISLAMIC ECONOMY - Yuniartik Yuniartik (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
This research is motivated by the practice of accounts payable for goods carried out by sellers to buyers. Seller owe the goods by asking for guarantees from the buyer and paying off the debt within the specified time for five months. As for the goods requested to be guaranteed in the form of gold and if the buyer does not pay off by the specified time limit, the buyer must give the gold to the seller as collateral, and the gold is held by the seller until the buyer pays it off, but the buyer must add costs as a fine due to the delay in paying the debt. as much as five percent with a period of five months must also be paid off. This type of research uses a type of library research ( library research ) that uses qualitative research methods. The approach method used in this study is a normative approach that refers to the norms or rules contained in the teachings of Islam. Based on the results of the study, it can be concluded that the practice of buying and selling goods paid for due with gold as collateral in Kupak Rebung Hamlet, Ratu Sepudak Village, Galing District, has fulfilled the pillars and conditions of the contract, the pillars and conditions of sale and purchase, the pillars and terms of accounts payable and the pillars and terms of the guarantee. However, the practice of buying and selling goods involves additional costs when due so that it contains elements of riba nasi'ah.